Genome-Wide Association Integrating a Transcriptomic Meta-Analysis Suggests That Genes Related to Fat Deposition and Muscle Development Are Closely Associated with Growth in Huaxi Cattle - Cheng-Li Liu; Tao Ren; Peng-Cheng Ruan; Yong-Fu Huang; Simone Ceccobelli; De-Jun Huang; Lu-Pei Zhang; Guang-Xin E (Veterinary Sciences)
Growth traits are among the most important economic phenotypes targeted in the genetic improvement of beef cattle. To understand the genetic basis of growth traits in Huaxi cattle, we performed a genome-wide association study (GWAS) on body weight, eye muscle area, and back fat thickness across five developmental stages in a population of 202 Huaxi cattle. Additionally, publicly available RNA-seq data from the longissimus dorsi muscle of both young and adult cattle were analyzed to identify key genes and genetic markers associated with growth in Huaxi cattle. In total, 7.19 million high-quality variant loci (SNPs and INDELs) were identified across all samples. In the GWAS, the three multilocus models (FarmCPU, MLMM, and BLINK) outperformed the conventional single-locus models (CMLM, GLM, and MLM). Consequently, GWAS analysis was conducted using multilocus models, which identified 99 variant loci significantly associated with growth traits and annotated a total of 83 candidate genes (CDGs). Additionally, 23 of the 83 CDGs overlapped with significantly differentially expressed genes identified from public RNA-seq datasets of longissimus dorsi muscle between young and adult cattle. Furthermore, gene functional enrichment (KEGG and GO) analyses revealed that over 30% of the pathways and GO terms were associated with muscle development and fat deposition, crucial factors for beef production. Specifically, key genes identified included MGLL, SGMS1, SNX29 and AKAP6, which are implicated in lipid metabolism, adipogenesis, and muscle growth. In summary, this study provides new insights into the genetic mechanisms underlying growth traits in Huaxi cattle and presents promising markers for future breeding improvements.